An analytical hierarchy process-based study on the factors affecting legislation on plastic bags in the USA. Issue 8 (August 2017) - Li, Zhongguo; Zhao, Fu
Annually, a large number of used plastic shopping bags are released into the environment, posing significant threats to public health and wildlife. Owing to these concerns, many local, regional, and national governments around the world have passed legislation to ban or restrict the use of plastic shopping bags. However, in the USA there are only 18 states that have approved plastic bag bans/fees, and even within these states these regulations do not cover all cities or counties. There are many factors that could affect the development and implementation of these regulations. This article employs an analytical hierarchy process to analyse the factors that could impact the enactment of plastic bag regulations. Five impact factors are identified based on statistical data, that is, geographical location, interest of industry achievable, cost of living, level of economic development, and educational level of population. The weights of the five impact factors are determined and it is found that the possibility of banning or restricting plastic bags in general follows a certain pattern among all states.